2019
DOI: 10.1002/jcb.28753
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Traf3 knockout liver cancer cell line using CRISPR/Cas9 system

Abstract: Purpose The gene editing technology in CRISPR/Cas9 system was used to construct the Traf3 knockout HepG2 cell line to explore the role of Traf3 in the development of liver cancer. Methods Five sgRNA sites were designed for the exons of Traf3. The recombinant plasmid of Lentiviral vector2‐Traf3‐sgRNA was constructed and transformed into Stbl3 competent cells. The recombinants were screened and sequenced, and the effectiveness of the designed gRNA was verified by sequencing. The constructed vector was transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…HepG2 cells, which highly express PGC-1α ( Fig. 5 C ) and are widely used for the experiment on genome editing ( 21 , 56 ) were used to examine the PGC-1α enhancer function by a genome editing approach. Single guide RNAs (sgRNAs) were designed to surround the C/EBPβ-binding sites in the two PGC-1α enhancer regions, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HepG2 cells, which highly express PGC-1α ( Fig. 5 C ) and are widely used for the experiment on genome editing ( 21 , 56 ) were used to examine the PGC-1α enhancer function by a genome editing approach. Single guide RNAs (sgRNAs) were designed to surround the C/EBPβ-binding sites in the two PGC-1α enhancer regions, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al found that CRISPR/Cas9-mediated gene deletion of Traf3 increased proliferation, migration, and invasion of HepG2 cells, providing valuable insights into Traf3’s function and mechanism [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, researchers conduct cell viability assays (such as MTT or MTS assays) after RP11-156P1.3 is knocked out in HCC cells [ 129 , 130 ]. As a result of RP11-156P1.3 knockout in HCC cells, they may report a significant drop in cell viability, quantified by a percentage.…”
Section: Methodsmentioning
confidence: 99%
“…The brown box represents the activation of different tumor suppressor genes. The orange box characterizes the inhibition/suppression of drug-resistance genes by CRISPR/Cas9 in solid tumors [ 31 , 35 , 45 , 70 , 74 , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.)…”
Section: The Potential Therapeutic Target Effects Of Crispr/cas9 In Smentioning
confidence: 99%